O profissional arquivista em instituição pública universitária: atribuições de responsabilidade social e ética perante a Lei de Acesso à Informação - Silva, Anna Carollyna de Bulhões Moreira (2016)
The necessity of informational democratization, such as, tools and resources that enable the reach of some required information, has become indispensable to reflect about professional duties that intermediate such process. In the field of archival information, this professional will be the archivist. Immersed in a public institutional reality, it arises some legal directions to be applied for, in due time the law of information access (LAI) that specifically contemplates the access and the secrecy of public information. It emerges the following research question: Which aspects the law of information access (LAI) and its guidelines can interfere with the archivist professional duties from public institutional universities in relation to social and ethic responsibility? This research aims to understand the archivist professional duties in the perspective of social and ethic responsibility before and after the law of information access published. The specific objectives are: to trace the archivist legislation and the LAI with the archivist reality; to determine the current duties form the archivist in front of the reality imposed by the LAI; to situate the previous and current archivist duties from Federal University from Paraíba (UFPB) in use of LAI; to identify the social and ethic posture from the archivist in the face of applied change of LAI. In methodological terms, this research is characterized as a case study because it seeks the reality of archivist professional at UFPB as a field survey. It uses bricolage as a strategy to contemplate lack of information from other researchers. The data collection is based on semi structured interviews to identify the qualitative nature of this research. In relation to data analysis, it uses the sense interpretation as a method that Minayo (2005) carrying out Norman Denzin words who defends as a comprehension possibility of social reality done by the range of its approach view. It can be elicited there are some real distance from the archivist and the LAI applicability and also the changes of professional duties in social and ethic responsibility aspects. The limitations are structural, people and their qualification. It affirms the lack of this career recognition at college. Thus, there is a real necessity to reframe the archivist parameters inside UFPB to attend the archivist providing services in order to get professional incentive and the archivist duties within a concept of social responsibility at university. Therefore, the archivist public policies might be constituted in a solid and multidisciplinary knowledge through the holistic view of the archival reality in this institution. It might be structured in accordance with all the professionals who work in archival centers. It must be indispensable to the archivists leadership and union in their career needs.